Corporate Finance and Investment / Decisions and Strategies - Neale Bill; Pike Richard (Prentice Hall, 1993)
This book addresses the main challenges in corporate finance today, examining issues primarily from the manager's viewpoint. Preface, Acknowledgements, A Framework for Financial Decisions, An Overview of Financial Management, The Financial Environment, Present Values and Wealth, Valuation of Assets and Shares and Companies, Investment Decisions and Strategies, Investment Appraisal Methods, Project Appraisal - Applications, Investment Evaluation in Practice, Analyzing Investment Risk, Relationships Between Investments: Portfolio Theory, Setting the Risk Premium: The Capital Asset Pricing Model, The Capital Investment Process, Financing Decisions and Policy, Sources of Finance, The Dividend Decision, Gearing and the Required Return, Capital Structure: The Underlying Relationships, Leasing Decisions, Working Capital Management and Theory, Integrated Topics: Overview, The Required Rate of Return on Investment, Managing Currency Risk, The Foreign Investment Decision, Identifying and Valuing Options, Acquisitions and Restructuring, References, Appendices, Index.